Корупційні схеми в оборонно-промисловому комплексі України: кримінологічний аналіз складових - Носач, А. В.; Nosach, A. V.; Поляков, І. С.; Poliakov, I. S. (Вісник Кримінологічної асоціації України. – 2024. – № 2 (32). – С. 166-179, 2024)
Стаття присвячена характеристиці корупційних схем в обороннопромисловому комплексі. Встановлено, що з початком повномасштабної агресивної війни росії проти України існуючі корупційні схеми в ОПК принципово не зазнали змін як такі. Змінилася динаміка їх функціонування, зазнали трансформації деякі корупційні узвичаєння, що були пов’язані з практиками обігу майна у мирний час. Змінились рівень та структура попиту на майно державних підприємств, що входять до ОПК. Однак ці зміни є кількісними, а не якісними. Корупційний функціонал у загальних своїх рисах лишився стабільним. Виявлено та надано опис таким корупційним схемам: привласнення виділених за оборонним замовленням коштів на закупівлю товарів і послуг у фіктивних підприємств, неіснуючих товарів і послуг; закупівлі товарів і послуг за завищеними цінами; укладання збиткових, заздалегідь не забезпечених виробничими можливостями, кредитних угод з подальшим відчуженням заставного майна; розтрата державного майна через укладання догорів оренди приватного майна зацікавлених у корупційній угоді осіб; передача в оренду державного майна на невигідних умовах, за заниженими цінами; неправомірне відчуження майна державних підприємств ОПК під прикриття процедури санації; отримання неправомірної вигоди за схвалення рішень про укладання державними підприємствами угод про пайову участь у капітальному будівництві на невигідних для таких підприємств умовах.

The article is devoted to the characteristics of corruption schemes in the defense-industrial complex. It was established that with the beginning of Russia's full-scale aggressive war against Ukraine, the existing corruption schemes in the defense industry did not fundamentally change as such. The dynamics of their functioning have changed, and some corruption customs, which were connected with the practices of property circulation in peacetime, have undergone a transformation. The level and structure of demand for the property of stateowned enterprises, which are part of the defense industry, have changed. However, these changes are quantitative, not qualitative. The corruption functionality in its general features remained stable. The following corruption schemes were identified and described: appropriation of funds allocated under a defense order for the purchase of goods and services from fictitious enterprises, non-existent goods and services; purchases of goods and services at inflated prices; conclusion of unprofitable loan agreements, which are not provided with production capabilities in advance, with subsequent alienation of collateral; appropriation of state property through the conclusion of lease agreements of private property of persons interested in the corruption agreement; leasing of state property on unfavorable terms, at reduced prices; unlawful alienation of the property of state-owned enterprises of the defense industry under the guise of the rehabilitation procedure; receiving an unlawful benefit for approving decisions on the conclusion by state enterprises of agreements on equity participation in capital construction on unfavorable terms for such enterprises.

Определены содержание и особенности функционирование коррупционных схем в оборонно-промышленном комплексе Украины.
Corruption schemes in the defense industrial complex of Ukraine: criminology analysis of the components
Keywords: корупція; корупційна злочинність; злочинність; корупційна схема; сектор безпеки та оборони; оборонно-промисловий комплекс; війна; протидія злочинності; corruption; corruption crime; crime; corruption scheme; security and defense sector; defense-industrial complex; war; combating crime; коррупция; коррупционная преступность; преступность; коррупционная схема; сектор безопасности и обороны; оборонно-промышленный комплекс; война; противодействие преступности